MO590: A Home-Based Exercise and Physical Activity Intervention After Kidney Transplantation: Impact of Exercise Intensity. The Phoenix-Kidney Study Protocol. (3rd May 2022) - Vandecruys, Marieke; De Smet, Stefan; Cornelissen, Véronique; Raes, Jeroen; De Geest, Sabina; Naesens, Maarten; Leunis, Sofie; De Beir, Jasmine; Vanden Wyngaert, Karsten; Nagler, Evi; Glorieux, Griet; Van Biesen, Wim; et al.
Abstract: BACKGROUND AND AIMS: Advances in the field of kidney transplantation have led to improved postoperative survival rates, but age-standardized mortality nonetheless remains 2- to 7-fold higher in kidney transplant recipients—with cardiovascular disease representing the leading cause of death in recipients with a functioning graft. Poor physical fitness, not completely recovering after transplantation, adds to the heightened cardiovascular risk of hypertension, diabetes, dyslipidemia and obesity. So does the post-transplant continuation of gut microbial dysbiosis, which recently emerged as a modulator of muscular, metabolic and cardiovascular health. Exercise-based rehabilitation and physical activity interventions may prove pivotal in the care of kidney transplant recipients to address aforementioned outcomes. METHOD: At 3 months post-transplant, a probability sample of 147 adult kidney transplant recipients from two independent Belgian transplant centers will be randomly allocated to either 6 months of home-based moderate-intensity training (MIT, n  = 49), concurrent moderate- and high-intensity training (MHIT, n  = 49) or usual care (CON, n  = 49) (Figure 1 ). High-intensity training sessions in MHIT are based on the Scandinavian model (four blocks of 4 min at high intensity interspersed by 3 min of active recovery), performed twice a week, and of equivalent energy expenditure as moderate-intensity training (Figure 2 ). MIT and MHIT will perform similar muscle strengthening exercises, twice a week. The training intervention will be followed by an individualized activity intervention aiming for long-term physical activity maintenance in MIT and MHIT; using motivational interviewing techniques, co-creation of an action plan adapted to the patients' preferences, goal-setting, gradually decreasing follow-up prompts over time and self-monitoring of physical activity behavior. Study participants will be followed-up till 2 years after transplantation. We hypothesize that the study intervention will improve our primary outcome cardiorespiratory fitness, assessed as peak oxygen uptake, at 9 months post-transplant. Secondary outcomes include muscle fitness, motor fitness, body composition, cardiovascular health, gut microbiome characteristics, health-related quality of life, safety, cost-effectiveness and implementation outcomes (Figure 1 ). The role of training intensity and the role of baseline gut microbiome characteristics as predictor of individuals' training response will be explored. RESULTS: Results from this two-phased RCT will provide novel insights in the safety, implementation potential, cost-effectiveness and effectiveness of a home-based exercise program and physical activity intervention in de novo kidney transplant recipients to improve physical fitness, cardiovascular health, gut microbiome characteristics and health-related quality of life. CONCLUSION: PHOENIX-kidney represents the first adequately powered multicenter RCT evaluating basic, clinical and health-economic outcome parameters in response to an exercise training and physical activity intervention in kidney transplant recipients.